The Development and Validation of a High-Resolution Photonic and Wireless System for Knee Gait Cycle Monitoring - Rui Pedro Leitão da Silva Rocha; Marcio Luís Munhoz Amorim; Melkzedekue Alcântara Moreira; Mario Gazziro; Marco Roberto Cavallari; Luciana Oliveira de Almeida; Oswaldo Hideo Ando Junior; João Paulo Pereira do Carmo (Applied System Innovation)
This paper presents the development and validation of a high-resolution photonic and wireless monitoring system for knee-referenced gait cycle analysis. The proposed system integrates a single optical Fiber Bragg Grating (FBG) sensor with a resonance wavelength of 1547.76 nm and electronic modules with inertial and magnetic sensors, achieving a 10 p.m. wavelength resolution and 1° angular accuracy. The innovative combination of these components enables a direct correlation between wavelength variations and angular measurements without requiring goniometers or motion capture systems. The system’s practicality and versatility were demonstrated through tests with seven healthy individuals of varying physical attributes, showcasing consistent performance across different scenarios. The FBG sensor, embedded in a polymeric foil and attached to an elastic knee band, maintained full sensing capabilities while allowing easy placement on the knee. The wireless modules, positioned above and below the knee, accurately measured the angle formed by the femur and tibia during the gait cycle. The experimental prototype validated the system’s effectiveness in providing precise and reliable knee kinematics data for clinical and sports-related applications.